2021
DOI: 10.3389/fphar.2021.735700
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Pharmacokinetics, and Pharmacodynamics of a Single Bolus of the γ-aminobutyric Acid (GABA) Receptor Potentiator HSK3486 in Healthy Chinese Elderly and Non-elderly

Abstract: Background: The present clinical trial investigated the potential influences of dosage and age on the pharmacokinetic properties and safety profile of HSK3486, and whether any adjustment in dosing regimen is necessary in elderly patients.Methods: Twenty-four elderly participants (65–73 years) were apportioned to three equal cohorts to receive a single IV bolus of 0.2, 0.3, and 0.4 mg/kg HSK3486, respectively. An additional control group comprised eight non-elderly participants (21–44 years), who each received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(61 citation statements)
references
References 22 publications
10
51
0
Order By: Relevance
“…Our data also suggest that ciprofol was associated with slightly less pronounced effects on the cardiovascular system, with its impacts on heart rate and blood pressure being non-inferior to those of propofol. Ciprofol was also significantly safer than propofol as indicated by the reduced incidence of intubation responses in this patient group, in line with prior preclinical work and findings from preliminary clinical efficacy studies [ 9 , 10 , 14 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our data also suggest that ciprofol was associated with slightly less pronounced effects on the cardiovascular system, with its impacts on heart rate and blood pressure being non-inferior to those of propofol. Ciprofol was also significantly safer than propofol as indicated by the reduced incidence of intubation responses in this patient group, in line with prior preclinical work and findings from preliminary clinical efficacy studies [ 9 , 10 , 14 ].…”
Section: Discussionsupporting
confidence: 85%
“…In general, ciprofol is associated with similar adverse side effects to those observed following propofol treatment, primarily affecting the respiratory and cardiovascular systems. There is also some evidence to suggest that ciprofol may exhibit lower rates of injection site pain and adverse respiratory effects as compared to propofol given that it is prepared at a lower concentration in the aqueous phase of the emulsion [ 10 ]. However, as ciprofol was only recently developed, limited data are currently available regarding its use for the induction of general anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma concentrations of HSK3486 and propofol were measured by validated liquid chromatography tandem mass spectrometry (LC-MS/MS) with a low limit of quantification (LLOQ) of 5 ng/mL. A plasma concentration below LLOQ was recorded as below the quantitation limit (BQL) [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…After initial evaluations of absorption, distribution, metabolism, and excretion (ADME) processes [ 19 ], the maximum concentration ( C max ), time to C max ( t max ), terminal elimination half-life ( t 1/2 ), and mean residence time (MRT) were similar between HSK3486 and propofol, while clearance (CL), apparent volume of distribution ( V d ) and apparent volume of distribution at steady state ( V ss ) were different in a phase 1 trial [ 20 ]. In addition, a study on age-related effects of HSK3486 revealed that a dose of 0.3 mg/kg was similarly efficacious in the elderly compared with 0.4 mg/kg in non-elderly patients [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…HSK3486 is a candidate intravenous drug that was developed for anaesthesia induction and maintenance ( Figure 1 ) [ 1–3 ]. HSK3486 has been investigated in several Phase I to III clinical trials that enrolled approximately 500 subjects, including healthy subjects, intensive care unit patients and those undergoing fibreoptic bronchoscopy, colonoscopy, gastroscopy, or elective surgery [ 2 , 4–6 ]. Results showed that the clinical characteristics of HSK3486 were comparable to propofol; the potency of HSK3486 was equivalent to propofol at 1/4 − 1/5 of the dosage; the plasma-level time curve for HSK3486 resembled that of propofol, and may be divided into three phases, an initial distribution phase (t 1/2α =2.0 min), a subsequent redistribution phase (t 1/2β =34.9 min) and a terminal elimination phase (t 1/2γ =6.2 h) [ 2 ].…”
Section: Introductionmentioning
confidence: 99%